The production of heritage : the politicisation of architectural conservation - Chandler, Alan, 1966-; Pace, Michela (2020)
"Is heritage a given, or is it produced? Is it for all or only for some, recognized by many but defined and coveted by a few? In this important book, the authors unpack the theoretical and practical issues around the development of heritage sites, critically dissecting key conservation benchmarks such as the ICOMOS guidelines, BS 7913 and the RIBA Conservation Plan of Work to reveal the mechanics of heritage guidance, its advantages and conceptual limitations. Underpinned by an active understanding of the conservation philosophy of William Morris, the book presents five case studies from the UK, North and South America that speak about different facets of heritage value, such as urban identity, commodification, authenticity, materiality, and heritage as an intellectual and ethical framework. Heritage is never neutral, its definition is privileged yet its influence is political. Art, Landscape and Archaeology all offer examples of how the operational ideas of adjacent disciplines can influence an integrated idea of heritage conservation, and how this is communicated in order to determine significance and share in its custodianship. This book provides insights into how to identify and challenge these limitations, expanding inclusion by describing tactics for changing how people can relate to, and build on the past. Clearly written for all levels of readership within the conservation professions and community custodians of heritage buildings and places, the book provides strategies and tactics for understanding the heritage significance of materials, their fabrication, detail and use. The narratives that historic fabric contains can help shape the meaningful involvement of local people, providing a roadmap for those navigating the double-bind of using the past to underpin the future"--
Introduction: heritage conservation in a neoliberal culture -- The production of heritage: philosophies of fabrication -- Place: material and the urban imaginary -- The memory of surfaces: the physical nature of visual memory and its illusion -- History and material significance: craft and a sense of place -- As found: tactics for away out of the heritage trap.
Includes bibliographical references and index.
Keywords: Historic preservation -- Political aspects; Historic preservation -- Case studies